Review of the list of LDCs - Udo E. Simonis (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2002)
The Committee for Development Policy is required by Economic and Social Council resolution 1991/46 to conduct triennially a review to determine the countries to be added or graduated from the list of least developed countries (LDCs). Since the previous review was conducted in 2000, the Committee conducted another review in 2003. The Committee bases its identification of the LDCs on the consideration of three dimensions of a country's state of development - its income level, its stock of human assets and its economic vulnerability. The Committee thus uses (a) Gross National Income (GNI) per capita as an indicator of income; (b) the Human Assets Index (HAI) as an indicator of the stock of human assets; and (c) the Economic Vulnerability Index (EVI) as an indicator of economic vulnerability. In addition, because the underlying concept of the LDC category excludes large economies, in 1991 the Economic and Social Council (ECOSOC) endorsed the principle that no country with a population exceeding 75 million should be considered for addition to the list.
Keywords: 300; Entwicklungsindikator; Vierte Welt